Post-keratoplasty glaucoma - S. A. Malozhen; S. V. Trufanov; S. Yu. Petrov (Oftalʹmologiâ)
Post-keratoplasty glaucoma (PKG) remains one of the leading causes of blindness due to the loss of optic nerve fibers and irreversible graft opacification. PKG is a challenge due to diagnostic and therapeutic difficulties and recalcitrant course. This paper reviews main pre-operative PKG risk factors such as pre-existing glaucoma, corneal disorders for which keratoplasty is performed, and lens status. Intraoperative errors that caused by ocular hypertension (tight suturing, larger trephine sizes, long bites of individual sutures, increased peripheral corneal thickness and graft-host disparity) are evaluated. Peripheral anterior synechiae, steroid use, and tonometry errors after deep anterior lamellar keraplasty are amongst post-operative causes of PKG. Partial transparency optical media, high post-operative astigmatism and graft edema make standard tonometry unreliable. Various tonometers and measurement reliability after keratoplasty are discussed. Currently, multiple treatment options including medications, laser and filtering surgery, glaucoma drainage devices and cyclodestructive procedures are available. In most cases of PKG, medications are initially prescribed. Evolution of approaches to PKG treatment as well as current therapy schedules, their advantages and ophthalmic complications are discussed. In cases non-responsive to medications, laser trabeculoplasty is performed. If laser procedures cannot be performed of their hypotensive effect is insufficient, glaucoma surgery is advised. A number of specialists prefer trabeculectomy with intra- or post-operative cytostatic adjunct. Glaucoma surgery with various drainage device implantation prevails. Ineffective surgery can be enhanced with transscleral laser cyclophotocoagulation.